How the European Union works : your guide to the EU institutions (Office for Official Publications of the European Communities LuxembourgLU, 2007)
Presents a brief overview of the agencies and other bodies that are involved in the European Union's work. Provides a helpful guide to EU decision-making.
Keywords: DECISION MAKING